Prey and predator density‐dependent interactions under different water volumes. Issue 11 (30th March 2021) - Cuthbert, Ross N.; Dalu, Tatenda; Wasserman, Ryan J.; Sentis, Arnaud; Weyl, Olaf L. F.; Froneman, P. William; Callaghan, Amanda; Dick, Jaimie T. A.
Abstract: Predation is a critical ecological process that directly and indirectly mediates population stabilities, as well as ecosystem structure and function. The strength of interactions between predators and prey may be mediated by multiple density dependences concerning numbers of predators and prey. In temporary wetland ecosystems in particular, fluctuating water volumes may alter predation rates through differing search space and prey encounter rates. Using a functional response approach, we examined the influence of predator and prey densities on interaction strengths of the temporary pond specialist copepod Lovenula raynerae preying on cladoceran prey, Daphnia pulex, under contrasting water volumes. Further, using a population dynamic modeling approach, we quantified multiple predator effects across differences in prey density and water volume. Predators exhibited type II functional responses under both water volumes, with significant antagonistic multiple predator effects (i.e., antagonisms) exhibited overall. The strengths of antagonistic interactions were, however, enhanced under reduced water volumes and at intermediate prey densities. These findings indicate important biotic and abiotic contexts that mediate predator–prey dynamics, whereby multiple predator effects are contingent on both prey density and search area characteristics. In particular, reduced search areas (i.e., water volumes) under intermediate prey densities could enhance antagonisms by heightening predator–predator interference effects. Abstract : Predator and prey densities are variable spatiotemporally across all habitat types globally. Our results indicate that predatory interaction strengths differ depending on densities of both predator and prey participants, with antagonistic multiple predator effects enhanced at intermediate prey densities. Future habitat changes resulting from anthropogenic activity that alter communities could have marked implications for trophic dynamics.